KONSEP ILMU PENDIDIKAN ISLAM DALAM AL-QUR’AN - Yan Yan Supriatman (FiTUA: Jurnal Studi Islam, 2021)
Muslims have made the Qur'an as a book that presents all instructions covering all aspects of life and is universal. By using qualitative research methods in the form of library research in this study, at least it can be found how the concept of Islamic education science with a philosophical study approach. The Qur'an in which discusses all aspects of human life, even the entire nature and all its contents are discussed in it. Especially in the field of education, Muslims make the basis of educational science both in terms of ontology, epistemology and axiology based on the Qur'an. This education is one of the efforts or actions to shape / guide humans because it is included in the scope of muamalah adabiyah. This education has an important meaning because it determines the pattern and form of charity and human life, both as individuals, social and divine beings. Islamic education with its various delivery methods and various learning materials aims to develop the nature of students, both spiritually, physically, willingly, and dynamically, so that a complete and supportive person will be formed for the implementation of his function as caliph fi al-ardh. So that Islamic education is tasked with guiding and developing students from stage to stage of life until they reach the point of optimal ability.